Resting right ventricular function in pectus excavatum: do haller index and age matter? - Choi, Jungsuk; Rim, Gongmin; Ahn, Seha; Lee, June; Jeong, Jin Yong (Frontiers in Surgery, 2025)
BackgroundPectus excavatum (PE) is associated with compression of intrathoracic structures, potentially impairing right ventricular (RV) function. The Haller index (HI) is widely used to quantify the severity of deformities; however, its functional correlation remains uncertain. This study aimed to evaluate whether HI and patient age were associated with resting RV systolic function in patients with PE.MethodsThis retrospective cohort study analyzed 67 patients with PE who underwent surgical correction and had complete preoperative echocardiographic data between January 2013 and January 2024. RV function was assessed using the fractional area change (FAC) and tricuspid annular plane systolic excursion (TAPSE). Patients were stratified by HI severity (<3.2, 3.2–3.4, ≥3.5) and age (≤13 vs. >13 years). Receiver operating characteristic (ROC) analysis and multivariate regression were used to determine predictors of RV dysfunction.ResultsThe mean HI was 4.09 (±0.99), and the mean age was 15.85 (±4.96) years. Neither HI nor age significantly correlated with FAC (HI: r = –0.04, p = 0.749; age: r = 0.09, p = 0.455) or TAPSE (HI: r = –0.05, p = 0.685; age: r = 0.14, p = 0.245). Subgroup and regression analyses confirmed that neither HI nor age were predictive of impaired RV systolic function. ROC analysis demonstrated the poor discriminatory power of age for reduced FAC (area under the curve = 0.478).ConclusionResting RV systolic function was not significantly influenced by HI or age in patients with PE. These findings highlight the need for a functional, individualized approach beyond anatomical metrics for surgical evaluation.